The Phenomenon of Religious Arbitrations in Family Law: Perceptions, Reality and Perspectives for the Future in England and Wales (TEST Trento Student Law Review, 2019)
Every day our increasingly multi-cultural societies experience new manifestations of cultural and religious diversity. The one I wish to address in this paper concerns the practice among members of close religious communities of recurring to religious courts to adjudicate family law disputes according to the principles and laws of their own faith. These decisions issued by religious courts, that are able to affect profoundly the life of the individual, may under certain circumstances become relevant to the legal system. I will refer to the phenomenon as religious or faith-based arbitration and I will argue in favour of its development in line with the theoretical basis provided for by the so-called ‘weak’ legal pluralism.Paragraph 2 of the paper is devoted to review the debate on religious arbitration in England and Wales, considering both its portrait in the press     and    the    major    academic   studies conducted   in  the  last  decade.  I  will  outline how many of the key questions remain unanswered, particularly for what concerns the definition of religious courts and their number on the British territory.I will examine the main points of connection between English family law and religious law, introducing the new trends for ‘out of court’ dispute resolution and specifically IFLA arbitration. Paragraph 3 is focused on arbitration, starting with an overview of the limits that the Arbitration Act 1996 imposes when parties agree on a religious law as the substantial law to be applied on their cases. I will then look in details at religious arbitrations concerning family law disputes, reviewing a recent judgement of the Family Court. I will conclude taking into account two areas where the current framework of arbitration laws, conceived to function in commercial purposes, appears to be inadequate to ensure an adequate protection of the parties.
Keywords: faith-based arbitration; family arbitration; religious courts; religious duress; gender-based discrimination